Document verification using quick response code with modified secure hash algorithm-1 and modified blowfish algorithm - Rogel Ladia Quilala; Theda Flare Ginoy Quilala (Institute of Advanced Engineering and Science, 2022)
A previous study has been conducted integrating modification on secure hash algorithm 1 (SHA-1) to document integrity verification of printed documents using quick response (QR) codes. However, encryption is warranted as data is transmitted in plaintext directly to the server to prevent hacking and ensuring not only data integrity but data security as well. A more secured document integrity verification using QR code was designed and developed by successfully incorporating a better hashing algorithm– modified SHA-1 and integrating a modern encryption algorithm–modified blowfish algorithm. By integrating both, data integrity and data confidentiality is assured as compared to previous research. The developed software was checked against user requirements to check the acceptability of the software. Error rate and accuracy were also checked to see how the software performed. Based on the testing conducted, it has been found that the document integrity verification software using QR code with the integration of modified SHA-1 hash and Modified Blowfish encryption was acceptable, accurate, and more secure.